Formation Mechanisms of Iron Oxide and Iron Sulfide at High Temperature in Aqueous H2S Corrosion Environment. Issue 3 (6th March 2018) - Gao, Shujun; Brown, Bruce; Young, David; Nesic, Srdjan; Singer, Marc
Abstract : Previous high temperature studies have shown that, in an oxygen-free aqueous H2 S environment, magnetite (Fe3 O4 ) forms as an inner layer while iron sulfides are found in the outer layer. Although magnetite is thermodynamically less stable than iron sulfide, it was always observed as a defined inner layer. In this work, experiments were conducted to investigate the formation mechanisms of magnetite and iron sulfide in an H2 S environment at high temperature. The corrosion behavior of mild steel was first investigated in environments with and without H2 S at pH 4.0 and 120°C, showing that magnetite is the dominant corrosion product layer in the initial stage of corrosion, due to a much higher saturation value than iron sulfide (mackinawite). In another experiment, the conversion of magnetite into mackinawite was investigated by exposing a preformed magnetite layer on an inert metal (nickel) to an H2 S environment. Consequently, it is postulated that Fe3 O4 experiences a simultaneous and continuous process of formation at the steel/magnetite interface and conversion to mackinawite at the magnetite/mackinawite interface. A descriptive model for the formation mechanisms of magnetite and iron sulfide at high temperature is presented.